Deformation and Failure Mechanism of Excavation in Clay Subjected to Hydraulic Uplift - Hong, Yi; Wang, Lizhong (Advanced Topics in Science and Technology in China,, 2016)
This book presents the latest experimental and numerical analysis work in the field of ground deformation and base instability of deep excavations in soft clay subjected to hydraulic uplift. The authors' latest research findings, based on dimensional analyses, well-instrumented full-scale field tests, systematic coupled-consolidation finite element analyses and centrifuge tests are reported. This book shows how to systematically approach a complex geotechnical problem, from identifying existing problems, reviewing literature, to dimensional and numerical analyses, validation through full-scale testing and centrifuge model testing. The methodologies are also introduced as major tools adopted in geotechnical research.